Performance Analysis of Line Operation Parameters and Customer Premises Equipment over a Very High-Bit-Rate Digital Subscriber Line 2 Network - Raden Sumarto, Raden Mohamad Syaifullah; Md Mustam, Saizalmursidi; Che Seman, Fauziahanim; Isa, Khalid; Zainal Abidin, Zuhairiah; Ramli, Khairun Nidzam; Hashim, Dang Fillatina (International Journal of Integrated Engineering, 2024)
Even though fiber networks have gained popularity today, Internet access via copper cable networks is still necessary in Malaysia, particularly in the suburban areas. This paper aims to examine the line operation parameters (LOPs) and customer premises equipment (CPE) performances over a very-high-bit-rate digital subscriber line 2 (VDSL2) network. These data are crucial in monitoring and preventing network faults and can be used as benchmarks during troubleshooting. In this paper, the LOPs data was obtained from the multi-service access node (MSAN) using the Xshell program. Data acquisition and extraction from the Huawei HG655m modem's Graphical User Interface (GUI), the CPE under investigation, was performed using a Python programming script. The statistical performance on network parameters such as actual line rate, line and signal attenuation, and signal-to-noise ratio (SNR) margin was then analyzed. In addition, the length of a bundle of ten twisted pairs of copper cable was varied for several distances: 100 m, 300 m, 500 m, 700 m, and 1000 m, with the operational bandwidth set to 17.664 MHz. The findings demonstrated an increment in the net data rates and packets by the Huawei HG655m modems received when a high-performance throughput is injected into the access network.